AB0097 Individual functions of the histone-acetyltransferases cbp and p300 in rheumatoid arthritis synovial fibroblasts - Lee, G.; Kolling, C.; Distler, O.; Ospelt, C.; Klein, K. (Annals of the rheumatic diseases, 2018)
BackgroundThe close homologues cAMP-response element binding protein (CREB) binding protein (CBP) and p300 are writers of H3K27 histone acetylation marks found in active enhancers. In addition, their bromodomains are readers of acetylated lysine residues on histone tails and are subject of drug development for inflammatory and malignant diseases. CBP and p300 are widely accepted as redundant proteins and unique functions have not been investigated yet in depth.ObjectivesTo analyse individual functions of CBP and p300 in rheumatoid arthritis synovial fibroblasts (SF).MethodsSF were treated with the pan inhibitor I-CBP (1 µM, 5 µM), targeting the bromodomains of CBP and p300, in presence and absence of TNF-α (10 ng/ml) for 24 hour. The expression of CBP and p300 was silenced by transfection of antisense LNA gapmeRs (5 nM) in SF. Knockdown was verified by Western blotting. 24 hour after transfection cells were stimulated with TNF-α (10 ng/ml) for 24 hour. The mRNA expression of potential target genes was measured by quantitative Real-time PCR, using RPLP0 as an endogenous control. The protein expression of HOXD10 after CBP and p300 silencing was verified by Western blotting.ResultsI-CBP dose-dependently reduced the TNF-α-induced expression of MMP1 (p<0,05), MMP3, IL6 and IL8 in SF (n=3). Antisense LNA gapmeRs targeting CBP reduced the protein expression of CBP by 68,7% (±12,9%, p<0,01, n=5) in unstimulated cells and by 89,7% (±12,9%) in presence of TNF-α. The protein expression of p300 was reduced by 55,3% (±29,8%, p<0,05, n=6) in unstimulated cells and by 62,7% (±27,9%) in presence of TNF-α after transfection of LNA gapmeRs targeting p300. Silencing of CBP in SF (n=7) reduced the TNF-α-induced expression of IL6 (p<0,05), IL8 (p<0,05), MMP3 (p<0,05), as well as the basal (p<0.001) and the TNF-α-induced expression of MMP1 (p<0,05). In contrast, silencing of p300 induced the basal expression of IL6 (p<0,05), IL8 (p<0,01), MMP1 (p<0,05), and MMP3 (p<0,05), as well as the TNF-α-induced expression of IL6 (p=0,078), IL8 (p=0,078), MMP1 (p<0,05) and MMP3 (p=0,063). Silencing of CBP in hand SF (n=4) reduced the expression of hand-specific HOX genes including HOXD10 (0,53±0,10 fold; p<0,01), HOXD11 (0,76±0,19 fold; p=0,098) and HOXA13 (0,75±0,17 fold; p=0,063), whereas HOXA9, HOXA10 and HOXA11 were not affected. Silencing of p300 reduced the expression of HOXD10 (0,65±0,24 fold; p=0,061), HOXD11 (0,45±0,10 fold; p<0,01), HOXA10 (0,70±0,14 fold; p<0,05) and HOXA13 (0,55±0,19 fold; p<0,05). The down regulation of HOXD10 after silencing of CBP and p300 in hand SF was confirmed on protein levels by Western blotting.Abstract AB0097 – Table 1CBP gapmeRCBP gapmeR+TNFp300 gapmeRp300 gapmeR+TNF MMP10,46±0,170,41±0,7525,86±26,821,96±1,35MMP30,97±0,310,64±0,352,60±1,623,05±2,89IL61,21±0,430,29±0,174,51±3,321,90±1,20IL88,27±9,700,52±0,20207,8±96,174,75±2,67ConclusionsOur results unravel opposing functions of CBP and p300 in regulating the TNF-α-induced expression of inflammatory and matrix-degrading target genes in SF. In addition, CBP and p300 likely contribute to the maintenance of a joint-specific gene expression in SF by regulating the expression of hand-specific HOX genes.AcknowledgementsMarie Heim Vögtlin grant (SNF), Stiftung für wissenschaftliche ForschungDisclosure of InterestG. Lee: None declared, C. Kolling: None declared, O. Distler Grant/research support from: Abbvie, Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone, Lilly, medac, MedImmune, Mepha, MSD, Mitsubishi Tanabe Pharma, Novartis, Pfizer, Pharmacyclics, Sanofi, Sinoxa and UCB, Consultant for: Abbvie, Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, iQone, Lilly, medac, MedImmune, Mepha, MSD, Mitsubishi Tanabe Pharma, Novartis, Pfizer, Pharmacyclics, Sanofi, Sinoxa and UCB, C. Ospelt: None declared, K. Klein Grant/research support from: Marie Heim Vögtlin grant (SNF)